Menguatkan Pendidikan Keuangan berbasis Islam: Analisis Pengaruh Environmental Social and Governance (ESG) terhadap Kinerja Saham dalam Pendidikan Keuangan - Nurheni, Siska; Nurfitri, Serlina; Kusumah, Dewita Febriyanti (UIR Press, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) on the stock performance of PT Unilever Indonesia Tbk during the period 2013–2023. The research uses a quantitative approach with a simple linear regression method and secondary data collected from annual reports, sustainability reports, and market data. Stock performance is proxied by Tobin’s Q as an indicator of firm value. The results indicate that ESG has a negative but statistically insignificant effect on Tobin’s Q. The R-squared value of 0.0730 shows that ESG explains only a small portion of the variation in firm value. These findings suggest that ESG practices have not yet been fully perceived by the market as a decisive factor in determining firm value. This study contributes to sustainable finance literature and provides implications for companies, investors, and regulators in strengthening ESG implementation and communication strategies